Pengaruh Penggunaan Media Elektronik terhadap Motivasi Belajar Santri di Pondok Pesantren Hidayatul Mubtadiin Tahun Pelajaran 2025/2026: Penelitian - Istiqomah, Anisa; Rohmiyati, Ummi; Istiqomah, Dedeh; Pujianti, Etika (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to analyze the influence of the use of electronic media at the Hidayatul Mubtadiin Islamic boarding school on the learning motivation of students at the Hidayatul Mubtadiin Islamic boarding school for the 2025/2026 academic year. This research uses descriptive qualitative methods with data collection techniques through interviews, observation and documentation (Miles & Hubermen 1994). The results of this research show how much influence the use of electronic media has on the motivation of students at the Hidayatul Mubtadiin Islamic boarding school. This has a big influence on the learning motivation of the students, so many things have to be improved so that the students will be able to use this media in a positive way